Security Assurance. - Lipner, Steven B. (Communications of the ACM, 2015)
The article discusses security assurance in computer programming as the author cites his experience developing such systems and how they meet customers' needs. He covers his work on software developer Microsoft's Security Development Lifecycle (SDL). In order to achieve practical assurance, the author suggests using continuous improvement practices, addressing the impact on delivered code, and considering the limitations of product liability and open source software.